Perancangan Sistem Informasi Layanan pada CU Saut Maju Nauli Berbasis Web - Livvran Parulian Pakpahan; Eva Julia G. Harianja; Rena Nainggolan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2026)
The advancement of information technology has driven various sectors to adopt digital solutions, including financial institutions such as Credit Unions (CUs). CU Saut Maju Nauli, located in Humbang Hasundutan Regency, still operates using a manual system to manage member data and savings-loan transactions. This manual process is prone to data entry errors, data loss, and slow service delivery. This study aims to design a web-based service information system to improve the efficiency and effectiveness of CU operations. The research adopts the Waterfall development method, with a case study approach and data collection through interviews, observations, and literature review. The system is designed to manage membership data, savings, loans, and installment payments in a structured manner. The result of this research is expected to assist CU administrators in providing faster, more accurate, and more efficient services.